Lobaplatin inhibits breast cancer progression, cell proliferation while it induces cell apoptosis by downregulating MTDH expression - Tian W; Hao S; Gao B; Jiang Y; Zhang X; Zhang S; Guo L; Zhao J; Zhang G; Chen Y; Li Z; Luo D (Dove Medical Press, 2018)
Wuguo Tian, Shuai Hao, Bo Gao, Yan Jiang, Xiaohua Zhang, Shu Zhang, Lingji Guo, Jianjie Zhao, Gang Zhang, Yi Chen, Zhirong Li, Donglin Luo Department of Breast, Thyroid Surgery, Research Institute of Surgery, Daping Hospital, Army Military Medical University, Chongqing 400042, China Objective: Lobaplatin shows antitumor activity against a wide range of tumors, including metastatic breast cancer (BCa). The overexpression of metadherin (MTDH) is associated with poor prognosis of BCa patients. This study was designed to investigate the effect of lobaplatin on MCF-7 cell proliferation and its association with MTDH expression.Patients and methods: Clinical treatment for BCa using lobaplatin, in combination with other general chemotherapy drugs, was administered to 32 BCa patients. The safety, effectiveness, and prognosis in lobaplatin-treated BCa patients were compared with those in controls (n=32). In vitro experiments were performed in MCF-7 cells to investigate the effect of lobaplatin on cell proliferation, apoptosis, and MTDH expression.Results: We found the intraoperative local chemotherapy using lobaplatin was safe and effective for BCa treatment, in comparison with the patients administered general chemotherapy drugs. Treatment of MCF-7 cell cultures with lobaplatin significantly reduced cell proliferation and increased cell apoptotic percentage. The expression of MTDH and Bcl-2 was inhibited by lobaplatin and that of Bax was increased by lobaplatin. Moreover, we observed the inhibition of MTDH by shRNA reduced cell proliferation and enhanced cell apoptosis.Conclusion: Lobaplatin was a safe and effective adjuvant chemotherapy for BCa. The effect of lobaplatin on inhibiting MCF-7 cell proliferation and inducing cell apoptosis might be, as least in part, mediated by suppressing the expression of oncogene MTDH. Keywords: breast cancer, lobaplatin, proliferation, apoptosis, MTDH